Interleaved Structured Sparse Convolutional Neural Networks - Xie, Guotian; Wang, Jingdong; Zhang, Ting; Lai, Jianhuang; Hong, Richang; Qi, Guo-Jun (The IEEE Conference on Computer Vision and Pattern Recognition (CVPR), 2018)
In this paper, we study the problem of designing efficient convolutional neural network architectures with the interest in eliminating the redundancy in convolution kernels. In addition to structured sparse kernels, low-rank kernels and the product of low-rank kernels,the product of structured sparse kernels, which is a framework for interpreting the recently-developed interleaved group convolutions (IGC) and its variants (e.g. , Xception), has been attracting increasing interests. Motivated by the observation that the convolutions contained in a group convolution in IGC can be further decomposed in the same manner, we present a modularized building block, [IGC-V2:]interleaved structured sparse convolutions. It generalizes interleaved group convolutions, which is composed of two structured sparse kernels, to the product of more structured sparse kernels, further eliminating the redundancy. We present the complementary condition and the balance condition to guide the design of structured sparse kernels, obtaining a balance between three aspects: model size and computation complexity and classification accuracy. Experimental results demonstrate the advantage on the balance between these three aspects compared to interleaved group convolutions and Xception and competitive performance with other state-of-the-art architecture design methods.